PEMBINGKAIAN BERITA BOIKOT PRODUK ISRAEL DI MEDIA ONLINE REPUBLIKA.CO.ID - Radhitya, Maurizza; Toni , Ahmad (STIE Mahardhika, 2024)
Republika is an online news portal founded by the Muslim community according to its readers. This news website is dominated by news which is dominated by news that contains Islamic elements. The aim of this research is to look for framing elements in 2 news articles written by the online media Republika.co.id. The research method used for analysis is Robert N. Entman's framing model, this analysis model has 4 elements, namely